ANALISIS YURIDIS PEMBUKTIAN UNSUR-UNSUR TINDAK KEJAHATAN GENOSIDA TERHADAP SUKU ROHINGYA DITINJAU DARI PASAL 6 STATUTA ROMA 1998 - S, Agrialdo Gamaliel; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Article 6 of the Rome Statute of 1998 provides an understanding of genocide, namelycrime with the intention of destroying in whole or in part a group based on nation, race,ethnicity or religion. The intended destruction can be done with various forms of crime: Killingmembers of the group, causing severe injuries or mental damage to group members,Deliberately threatening the lives of group members that cause physical injuries both in part andin whole, Perform actions intended to prevent births in groups, Forcibly transferring childrenfrom one group to another. The Myanmar government is alleged to have committed violenceagainst body and soul, murder, hostage taking, rape for personal honor. But this has not yetbeen completed and there is no certainty regarding genocide to Rohingya ethnic groups. Indeed,to prove it according to the Rome Statute is quite difficult because Myanmar has not ratified theRome Statute. Myanmar has also not officially reported whether they conducted an investigationand or legal effort. Because in Article 51 of the Rome Statute to prove that there must be a partyconcerned (Myanmar).Scientific writing aims to: First, to find out the elements of genocide crime committed byMyanmar against Rohingya ethnicity. Second, to find out the proof of the elements of thegenocide crime against the Rohingya ethnicity, reviewed in Article 6 of the Rome Statute of1998.The writing of this paper uses normative legal research methods by pointing to thehistory of law which describes the history of genocide and the causes of genocide crimescommitted by Myanmar, where the writing collected data from literature, related regulations,related documents and analyzed using qualitative methods to draw conclusions.From the results of this research, to prove that genocide elements in Myanmar first paidattention to whether Myanmar had conducted a trial of genocide perpetrators, it turned out thatthere was no trial there, so that the International Criminal Court (ICC) conducted aninvestigation directly into Myanmar to prove the existence of genocide there.Keyword : Rohingya, Genocide, Interntional Criminal Court